The application of haplotypes instead of species-level ranks modifies the interpretation of ecological preferences in lichen symbiont interactions in Parmelia - Emilia Anna Ossowska; Beata Guzow-Krzemińska; Martin Kukwa; Jiří Malíček; Ulf Schiefelbein; Arne Thell; Magdalena Kosecka (Scientific Reports, 2024)
Abstract The analysis of the interaction between main bionts (mycobiont and photobiont) in the lichen symbiosis delivers substantial information about their preferences in the selection of symbiotic partners, and their ecological preferences. The selectivity in the Parmelia genus has been defined as strong so far. However, data on this lichen genus, which includes several widely distributed species, are biogeographically limited. Therefore, using specialization indicators and extended sampling, in this study, we estimated the interactions between the main bionts of selected Parmelia spp., using two levels of estimation (species/OTU and haplotype). A comparison of mycobiont-photobiont interactions at different levels showed that considering only mycobiont species and Trebouxia OTUs, greater specialization is found, while Parmelia species studied in this work present a more generalistic strategy in photobiont choice when haplotypes are considered. Despite the uneven sampling of Parmelia species, the interpretation of specialization within species and individuals of the genus leads to a more precise and accurate interpretation of their adaptation strategies. Furthermore, the data from P. sulcata indicate the existence of a different pool of compatible haplotypes in some geographical regions compared to neighboring areas. This observation suggests the potential influence of climatic factors.